Fostering the Cultural Identity of the Tibetan Diaspora in Dharamshala: a case of Cultural Preservation through Tourism - Lakhani, Sanjana (SPA Bhopal, 2025)
Dharamshala is a city in Himachal Pradesh, which falls in the Kangra district. The city is home to the refugees from Tibet who initially arrived in India seeking protection from Chinese rule. In 1959, during the Lhasa Uprising, the 14th His Holiness Dalai Lama fled to India with around 30,000 Tibetans. Since they arrived in India, the Tibetans have been trying to find a home away from home. This Tibetan diaspora currently resides in many parts of India in around 40 formal settlements and many more informal settlements controlled and monitored by the Central Tibetan Administration. The headquarters of this Tibetan diaspora is in McLeod Ganj, Dharamshala, also known as ‘Little Lhasa’, where their spiritual leader currently resides. The Urban Form here has been constantly shaped by the arrival of Tibetans over three waves of migration. This thesis delves into the evolution of Dharamshala's urban fabric, under the influence of the Tibetan diaspora. The thesis inquiry is to understand the Cultural Anthropology of a diaspora with no land security and prescribe Urban Design measures to preserve their Cultural Identity in their home away from home. Dharamshala, one of the biggest and most important Tibetan settlements, has been taken as the city to demonstrate this Cultural Preservation. This thesis aims to provide Urban Design Guidelines for developing the public realm, considering the cultural variance between the host community and the diasporic community. The primary focus is to preserve the cultural identity of the diaspora through tourism while fostering cultural exchange. This thesis primarily focuses on cultural exchanges through tourists since they can help increase the diaspora's cultural reach. This thesis proposes an integrated Tourist Circuit for Upper Dharamshala connecting to all the city's major attractions. The area of focus is McLeodganj where the city’s tourism can be promoted by leveraging Foreign tourist footfall due to Tibetan culture. The objective is also to give Urban Design Strategies for Temple Road in McLeod Ganj. The thesis also suggests the Form-Based Codes for the existing Tibetan neighborhood.
Keywords: Cultural Anthropology; Urban Design Guidelines; Dharamshala; Himachal Pradesh